Correlation analysis of DLG5 and PD-L1 expression in triple-negative breast cancer - Jingmin Che; Bo Chen; Xusheng Wang; Baoe Liu; Cuixiang Xu; Huxia Wang; Jingying Sun; Qing Feng; Xiangrong Zhao; Zhangjun Song (BMC Cancer)
Abstract Background Triple-negative breast cancer (TNBC) is among the most aggressive forms of breast cancer, characterized by a dismal prognosis. In the absence of drug-targetable receptors, chemotherapy remains the sole systemic treatment alternative. Recent advancements in immunotherapy, particularly immune checkpoint inhibitors (ICIs) that target programmed death 1/programmed death ligand 1 (PD-1/PD-L1) and cytotoxic T lymphocyte associated antigen 4 (CTLA-4), have provided renewed optimism for the treatment of patients with TNBC. Prior research has indicated that the expression level of the cell polarity protein discs large homolog 5 (DLG5) correlates with the malignant progression and prognosis of breast cancer; nevertheless, its influence on PD-L1 expression and its function in immunotherapy for TNBC require further investigation. Methods The hypoxia cell model was established by simulating the cell hypoxic microenvironment in the human SUM159 and MDA-MB-231 cell lines using cobalt II chloride (CoCl2). A combination of PD-L1 inhibitors and DLG5 RNA interference techniques was used, along with various methods including cell counting kit-8 (CCK-8), colony formation, wound healing, transwell migration, reverse transcription-quantitative real-time PCR (RT-qPCR), immunofluorescence, immunohistochemical staining (IHC), expression analysis from datasets and western blotting. These methods were employed to evaluate changes in cell proliferation, migration, and the expression levels of PD-L1 and DLG5. Additionally, the correlation between the expression of PD-L1 and DLG5 in clinical samples was analyzed. Results (1) In vitro experiments, a cellular hypoxia model was effectively established utilizing 150 µM CoCl₂. Under these conditions, cell clone formation, invasiveness, and migration rate were all significantly inhibited. (2) The expression levels of DLG5 and PD-L1 were significantly increased in both MDA-MB-231 and SUM159 cells following treatment with 150 µM CoCl₂. (3) Silencing DLG5 resulted in a considerable upregulation of PD-L1 expression in MDA-MB-231 and SUM159 cells under normoxic circumstances, but it was markedly downregulated under hypoxic settings. Inhibition of PD-L1 expression resulted in a considerable increase in DLG5 expression under normoxic conditions, but it decreased under hypoxic conditions. Correlation research demonstrated an inverse association between the expression of DLG5 and PD-L1 in TNBC tissues. Conclusion This study provides new theoretical evidence and potential therapeutic targets for the immunotherapy strategies of TNBC, holding significant clinical application value.